Messianism ideas of "Big emigration" in Poland's Prometheism concept of the 1920s - 1930s - Volodymyr Komar (Cхід)
The article deals with the influence of "Big Emigration" ideas (A. Mitskevych's ideas, in particular) on the formation of the prometheism concept, which envisaged the USSR disintegration into separate national states with their subsequent federation with Poland.